Strategi Komunikasi Ferry Irwandi dalam Membangun Personal Branding di YouTube - Muhammad Adnan Faidh; Arfian Surya Suciramdhan; Muhamad Fauzan Kurniawan; Aldo Savero Zahran; Rian Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze Ferry Irwandi’s communication strategies in building personal branding on the YouTube platform. Ferry Irwandi was selected as a case study due to his success in constructing an authentic self-image through consistent spiritual and reflective narratives, as well as his strong engagement with a young adult audience. This research employs a qualitative approach using a case study method, involving video content observation, social media documentation, and in-depth interviews with both the subject and his audience. The findings reveal that Ferry Irwandi’s communication strategy is built upon four main pillars: narrative storytelling, message consistency, visual branding, and active audience engagement. These results highlight the significance of authentic narratives, consistent digital identity, and emotional interaction in developing a sustainable personal brand on social media.